Microstructures and Electrochemical Behavior of Ti-Mo Alloys for Biomaterials - Back-Sub Sung; Tae-Eon Park; Young-Hoon Yun (Advances in Materials Science and Engineering)
The Ti alloy with 7 wt% Mo revealed a microstructure that contained only the orthorhombic α′′ phase of a fine acicular martensitic structure. The corrosion resistance of the Ti-Mo alloys increased as the Mo content increased. Based on the results obtained from the polarization curve and electrochemical impedance, the Ti-Mo alloys were shown to be corrosion resistant because of the passive films formed on their surfaces. No ion release was detected in SBF (simulated body fluid) solution, while Ti ions were released in 0.1% lactic acid ranging from 0.05 to 0.12 μg/mL for the Ti-Mo alloys. In vitro tests showed that MC3T3-E1 cell proliferation on Ti-7 wt% Mo alloy was rather active compared to other Ti-Mo alloys and commercial-grade pure Ti.